Upaya Peningkatan Pengetahuan dan Sikap Siswa SMA Negeri 1 Margahayu Terhadap Pencegahan Serangan Jantung Koroner - Budi Rustandi; Theophylia Melisa Manumara; Nesa Regina Noviyanti; Faiza Sausan Karinda; Zalva Febriana Sukardi; Salsa Nurliawati; Rifki Nurohman; Flora Cinta Anggraini; Inge Parasningtias Billah; Farla Meitha Zahra; Anggun Nadila; Bagas Dinan Maulana; Albar Rizki Suwita Nardy; Nur Aeni Mukti (Jurnal Medika: Medika, 2026)
A coronary heart attack is a medical emergency caused by the interruption of blood flow to the heart muscle, resulting in tissue damage and potentially leading to serious complications. The lack of knowledge among adolescents about risk factors, signs and symptoms, and prevention of coronary heart attacks is the reason why early education is necessary. This health education activity aims to improve students' understanding of coronary heart attacks so that they can recognize the risks and adopt healthy lifestyles. The method used is interactive education conducted at Margahayu 1 Public High School, involving 30 students. The material was delivered through lectures, discussions, educational videos, leaflet distribution, and question and answer sessions, preced ed by a pre-test and followed by an evaluation of participants' understanding. The results of the activity showed that students were very enthusiastic about participating in the entire series of educational activities, were able to answer questions related to the material, and understood the causes, signs and symptoms, and preventive measures for coronary heart attacks. This activity had a positive impact in the form of increased student awareness of the importance of maintaining heart health and preventive measures that can be taken from adolescence. Thus, this type of health education is important to continue as a promotional effort in preventing cardiovascular disease in the future.